The validity of the other knowledge for Bacon: Greeks and Romans of antiquity and the Native Americans - Solano Villareal, Diana (2019)
This article is about the vision of Francis Bacon regarding the validity ofother knowledge, the case of the Greeks and Romans in Antiquity and NativeAmericans for the 16th century. It is intended to analyze the validity that forF. Bacon would have the knowledge produced by the Greeks, Romans andNative American cultures and its relationship with the domain in our days,in his works The Advancement of Learning, Preparation for a Natural andExperimental History, Valerius terminus: or the interpretation of nature andDignitate et Augmentis Scientiarum from the theory of the group modernity/coloniality in the decolonial studies of colonial.